1986
DOI: 10.1038/ki.1986.201
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of uric acid nephrolithiasis with potassium citrate

Abstract: Eighteen patients with uric acid nephrolithiasis (six with uric acid stones alone and 12 with both uric acid and calcium stones) underwent long-term treatment (1 to 5.33 years, mean of 2.78 years) with potassium citrate (30 to 80 mEq/day, usually 60 mEq/day). Urinary pH increased from low (5.30 +/- 0.31 SD) to normal (6.19 to 6.46) during treatment. Urinary content of undissociated uric acid, which was high to begin with at 204 +/- 82 mg/day, decreased to the normal range (64 to 108 mg/day) following treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
5

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(62 citation statements)
references
References 19 publications
1
56
0
5
Order By: Relevance
“…Citrate retards the crystallization of stone-forming salts through two mechanisms. First, it forms a soluble complex with calcium and reduces ionized calcium concentration, thereby reducing calcium oxalate and calcium phosphate supersaturation (6). The second mechanism is the direct inhibitory effect of citrate on spontaneous nucleation, crystal growth, and crystal agglomeration of preformed calcium oxalate crystals (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrate retards the crystallization of stone-forming salts through two mechanisms. First, it forms a soluble complex with calcium and reduces ionized calcium concentration, thereby reducing calcium oxalate and calcium phosphate supersaturation (6). The second mechanism is the direct inhibitory effect of citrate on spontaneous nucleation, crystal growth, and crystal agglomeration of preformed calcium oxalate crystals (19).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in urinary citrate retards spontaneous nucleation and agglomeration of calcium oxalate crystals (5). Moreover, by increasing urinary pH and decreasing urinary content of undissociated uric acid, this treatment is useful in preventing uric acid stones (6).…”
mentioning
confidence: 99%
“…UAN is highly associated with low urinary pH and urine volume, hyper- or normouricosuria, and the increased incidence of diabetes or insulin resistance [6,7,8,9,10]. Pharmacological treatment with potassium or sodium citrate has been proven to increase urinary pH and inhibit UA stone formation, providing further evidence that UAN is linked to low urinary pH [11,12,13,14]. Patients with diabetes and UAN not only have low urinary pH values, but also exhibit decreased renal ammonium excretion.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute difference in pH, 0.28, was not as great as that (0.55 to 0.85) observed by Pak and Peterson 18 when treating patients with hyperuricosuric calcium stone formation. Pak et al 19 also observed a much greater increase in pH (0.9) with citrate therapy when treating patients with uric acid stone formation.…”
Section: Commentmentioning
confidence: 93%